Efficacy of short-term nivolumab treatment in a Chinese patient with relapsed advanced-stage lung squamous cell carcinoma: A case report. Issue 40 (October 2016) - Pi, Guoliang; He, Hanping; Bi, Jianping; Li, Ying; Li, Yanping; Zhang, Yong; Wang, Mingwei; Han, Guang; Lin, Chi
Abstract: Introduction: Currently, the options are limited for the treatment of patients who have failed 2 lines of chemotherapy for advanced lung squamous cell carcinoma (SCC). Recently, nivolumab, a fully human IgG4 programmed death 1 immune checkpoint inhibitor antibody, was approved to treat patients with advanced stage, relapsed/refractory lung SCC. Although nivolumab has demonstrated antitumor activity with survival benefit in Caucasian patients, its efficacy in Asian patients is unknown. Case Report: In this report, we describe a Chinese patient with relapsed advanced stage lung SCC who had an excellent response to nivolumab after only 2 doses without any adverse effects. Immunohistochemical analysis indicated the tumor was stained positive for programmed death-ligand 1. Conclusion: To our knowledge, this is the first report of satisfactory efficacy of short-term nivolumab treatment in a Chinese patient with relapsed advanced-stage lung SCC. Further clinical trials in Asian countries are needed to test whether nivolumab immunotherapy is a safe and effective treatment for Asian patients with lung SCC.